Pengaruh Variasi Latihan Permainan Di Air Terhadap Keterampilan Gerak Dasar Renang Gaya Bebas Siswa Sekolah Menengah Pertama - Rahmawati, Ineke Hanny; Rahayu, Ega Trisna; Nugroho, Setio (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2024)
This study uses quantitative research methods with a one-group experimental design to explore the impact of water game training on basic freestyle swimming skills in students participating in beginner-level swimming extracurricular activities. Study participants consisted of 14 students who took part in a training program for 8 sessions. Data were collected through basic swimming skills tests and analyzed using normality, homogeneity and T tests. The results of the analysis showed a significant increase between the pretest and posttest scores with a significance level of less than 0.05, and the results of the T table of more than 2.160 confirmed that training Water games are effective in improving freestyle swimming abilities in beginner students at junior high school level